2013
DOI: 10.1099/vir.0.055673-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel spliced gene in alcelaphine herpesvirus 1 encodes a glycoprotein which is secreted in vitro

Abstract: Herpesviruses often contain cryptic, spliced genes that are not obvious from the initial in silico annotation. Alcelaphine herpesvirus 1 (AlHV-1) contains 72 annotated ORFs but there are also a number of gaps between these that may have protein-coding potential. Comparative analysis of coding potential between AlHV-1 and the related ovine herpesvirus 2 (OvHV-2) revealed a putative novel spliced gene that we have termed A9.5. Analysis of cDNA clones from AlHV-1-infected cells revealed three overlapping clones c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…Each set of assays was controlled by the inclusion of known AlHV-1 positive and negative bovine genomic DNA samples and potential cross-contamination between reactions was controlled by the inclusion of template-free reactions. To study viral variation in positive samples, segments of the ORF50 gene, encoding the lytic cycle trans-activator protein, and of the spliced A9.5 gene [ 24 ] were sequenced and analysed as described previously for OvHV-2 [ 25 ]. ORF50 encodes a transcription factor expected to be highly conserved, whilst A9.5 encodes a predicted glycoprotein of unknown function that has been demonstrated to be polymorphic in both AlHV-1 and OvHV-2 [ 25 ],[ 24 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Each set of assays was controlled by the inclusion of known AlHV-1 positive and negative bovine genomic DNA samples and potential cross-contamination between reactions was controlled by the inclusion of template-free reactions. To study viral variation in positive samples, segments of the ORF50 gene, encoding the lytic cycle trans-activator protein, and of the spliced A9.5 gene [ 24 ] were sequenced and analysed as described previously for OvHV-2 [ 25 ]. ORF50 encodes a transcription factor expected to be highly conserved, whilst A9.5 encodes a predicted glycoprotein of unknown function that has been demonstrated to be polymorphic in both AlHV-1 and OvHV-2 [ 25 ],[ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Primers for nested PCR of the A9.5 gene were designed to target conserved areas flanking the predicted coding region, based on the available sequence of AlHV-1 [ 31 ],[ 24 ]. Primers for amplification of ORF50 (AHVorf50_F, GCC AGG CAG AGG TAT GTG TT and AHVorf50_R, GGC CGT TGT GGG TAC TGT AT) were chosen within exon 2 of the ORF50 gene, to amplify a fragment of 543 base pairs for analysis of sequence variation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aims of this work were to confirm the interaction of mAb 12B5 with AlHV-1 gB by expression of a recombinant, epitope tagged polypeptide and to characterise the expression and antigenicity of the recombinant gB polypeptide. Human embryonic kidney 293T (HEK293T) cells were used for transfection studies following previous experiments that had shown that this cell line provided both a high frequency of transfection and a high level of expression of MCF virus genes 17,18 . For transfection and subsequent protein expression, cells were grown in IMDM with 10 % FBS and 2 % L-glutamine.…”
Section: Introductionmentioning
confidence: 99%